ЛЕКСИКО-СТИЛІСТИЧНІ ЗАСОБИ ВИРАЖЕННЯ ОБРАЗУ АВТОРА ГАЗЕТНОГО ДИСКУРСУ (НА МАТЕРІАЛІ БЛОГІВ ГАЗЕТИ “МОЛОДИЙ БУКОВИНЕЦЬ”) - Анотофійчук, Алла Миколаївна; Вівчарюк, Галина Романівна (Чернівці -- Сучава: БДМУ, 2022)
The objective of the article is to determine, systemize and analyze the lexical and stylistic means of implementing the category “the image of the author of newspaper discourse”, relying on the material of blogs of the newspaper “Molodyi Bukovynets”. The significance of the research under studies has been stipulated by the necessity of a profound investigation of the nature of newspaper discourse, and particularly – the ways the image of the author is implemented through various lexical and stylistic means. The novelty of the paper lies in a detailed analysis of lexical and stylistic means, which are the markers of the author’s point of view in the texts of newspaper blogs. In the article, both universal scientific (analysis, synthesis, description, generalization, specification, explanation) and linguistic (structural-semantic, functional-stylistic, contextual, typological) methods have been applied. Conclusions. The linguistic category of the image of the author is pervasive in newspaper discourse. It might be found at every linguistic level, as well as is presented by a broad range of lexical and stylistic means. In comparison with other linguistic levels, the lexical and stylistic ones possess a far greater number of opportunities to express the author’s modality. Among the stylistic means, metaphor is used much more frequently than metonymy, synecdoche and various types of comparison. While neologisms are used in newspaper texts quite often with the purpose of reflecting today’s realities, the outdated vocabulary and dialectisms are applied with certain stylistic aims. The imagery of the language of newspaper blogs is also represented by numerous stylistic figures, the latter serving as a kind of markers of the author’s perception of newspaper information. The linguisti category of the image of the author is a favorable source of substantiating the anthropocentric concept of linguistic research, as well as possesses broad prospects for systemizing the means of presenting the author’s point at other linguistic levels.
LEXICAL AND STYLISTIC MEANS OF EXPRESSING THE IMAGE OF THE AUTHOR OF NEWSPAPER DISCOURSE (ON THE MATERIAL OF BLOGS OF THE NEWSPAPER “MOLODYI BUKOVYNETS”)
Keywords: newspaper discourse; newspaper text; the category of the image of the author; author’s modality; blog; lexical and stylistic means